Human Adipose-Derived Mesenchymal Stem Cell-Secreted CXCL1 and CXCL8 Facilitate Breast Tumor Growth By Promoting Angiogenesis. (5th June 2017) - Wang, Yuan; Liu, Junli; Jiang, Qingyuan; Deng, Jie; Xu, Fen; Chen, Xiaolei; Cheng, Fuyi; Zhang, Yujing; Yao, Yunqi; Xia, Zhemin; Xu, Xia; Su, Xiaolan; et al.
Abstract : Autologous adipose tissue or adipose tissue with additive adipose-derived mesenchymal stem cells (ADSCs) is used in the breast reconstruction of breast cancer patients who undergo mastectomy. ADSCs play an important role in the angiogenesis and adipogenesis, which make it much better than other materials. However, ADSCs may promote residual tumor cells to proliferate or metastasize, and the mechanism is still not fully understood. In this study, we demonstrated that human ADSCs (hADSCs) could facilitate tumor cells growth after co-injection with MCF7 and ZR-75-30 breast cancer cells (BCCs) by promoting angiogenesis, but hADSCs showed limited effect on the growth of MDA-MB-231 BCCs. Intriguingly, compared with ZR-75-30 tumor cells, MCF7 tumor cells were more potentially promoted by hADSCs in the aspects of angiogenesis and proliferation. Consistent with this, cytokine and angiogenesis array analyses showed that after co-injection with hADSCs, the CXCL1 and CXCL8 concentration were significantly increased in MCF7 tumor, but only moderately increased in ZR-75-30 tumor and did not increase in MDA-MB-231 tumor. Furthermore, we found that CXCL1/8 were mainly derived from hADSCs and could increase the migration and tube formation of human umbilical vein endothelial cells (HUVECs) by signaling via their receptors CXCR1 and CXCR2. A CXCR1/2-specific antagonist (SCH527123) attenuated the angiogenesis and tumor growth in vivo. Our findings suggest that CXCL1/8 secreted by hADSCs could promote breast cancer angiogenesis and therefore provide better understanding of safety concerns regarding the clinical application of hADSCs and suggestion in further novel therapeutic options.